ArchBukhta 24 Hours. Beyond the limits of the possible - Anisimova, Alevtina; Malinovich, Roman (project baikal, 2025)
From 28 February to 2 March 2025, the XIX All‑Russian Architectural Festival “ArchBukhta. 24 Hours” took place. Organised by the Club of Young Architects, the Festival has long been a significant event in the world of creative people. This year the venue brought together 17 teams from six Russian cities: Moscow, St. Petersburg, Samara, Omsk, Novosibirsk and Irkutsk. In total, 100 talented architects, students, designers and professional practitioners took part in creating art objects.
Keywords: ArchBukhta; art object; 24 hours; creativity; Listvyanka; Baikal; ice